STUDENTS’ VIEWPOINT: EARLY 21ST CENTURY SKILLS IN ENGLISH AREA IN MAJENE REGENCY - Nugroho, Dwi Adi; Hustiana, Hustiana; Asdar, Asdar; Ikhsan, (ENGLISH JOURNAL, 2024)
This deconstruction sought to determine students' views on the implementation of English Area on their English language skills and early 21st century skills. English Area was executed because seeing the situation in Majene Regency, there were still many students who lack English skills. In addition, students did not yet have a place to study after school hours end. This program was applied to improve their abilities, namely early 21st-century skills that are associated with English learning. This study wss descriptive quantitative where the instruments employed in this study were questionnaires and observation guides. The questionnaire used contains six indicators of early 21st-century skills, namely collaboration, communication, creativity, critical thinking, character and collecting information. This study involved 28 students of grade VIII SMA 3 Majene. The results showed that the English Area program was able to improve collecting information skills with a value of 4.33, followed by collaboration and character skills with a value of 4.28. Therefore, further research needs to be done to enhance other early 21st-century skills associated with only one English skill so that the results are more significant. Keywords: Students' Viewpoint, English , Early 21st Century Skills, English Area